Autologous matrix-induced chondrogenesis and bone marrow aspirate concentrate compared with microfracture for arthroscopic treatment of femoroacetabular impingement and chondral lesions of the hip: bridging the osteoarthritis gap and facilitating enhanced recovery. Issue 3 (13th October 2020) - Sobti, Anshul S; Baryeh, Kwaku W; Woolf, Rex; Chana, Rishi
Abstract: In an attempt to bridge the osteoarthritis (OA) gap, this study compared biological reconstruction with traditional microfracture (MF) techniques in patients with femoroacetabular impingement and focal cartilage defects. Cohorts of two groups were investigated; age, gender and Tonnis grade matched comparison for outcomes between MF and newer biological reconstruction techniques hip arthroscopy surgery using autologous matrix-induced chondrogenesis and bone marrow aspirate combination. Outcomes investigated were pre-op and post-op mean iHOT-12 scores up to 18 months after surgery with a Kaplan–Meier survivorship analysis. Of 111 patients, 46 patients underwent MF and 65 biological reconstruction hip arthroscopy including cam/pincer osteoplasty and labral repair surgery. Age range was 20–69, mean age 45 years for both groups, Tonnis grading was as follows: Grade 0: 26% versus 30%, Grade 1: 52% versus 47% and Grade 2: 22% versus 23% in MF and biological reconstruction groups, respectively. The mean post-operative iHOT-12 score differences between MF and biological reconstruction were significant at 1-year minimum follow-up ( P = 0.01, SD 2.8). Biological reconstruction allowed for an enhanced recovery protocol. The MF group had a 67.4% survivorship for conversion to hip replacement at 18 months (32.6% failure rate for any reason) and biological reconstruction had 100% survivorship at 18 months post-operatively with no failures for any reason. This study provides further support to the evidence base for biological reconstructive techniques as superior to MF in combination with joint preservation arthroscopic surgery, even in the face of focal cartilage defects and offers both surgeons and patients a potential bridging of the OA gap.